THE EVOLUTION OF TRANSACTIONAL FINANCE: AUTOMATION, REAL-TIME PAYMENTS, AND STRATEGIC TRANSFORMATION (2018 – 2025) - Amin, Niyati; Satsangi, Priya; Padroo, Bhawna Sharma (International Journal of Engineering Technologies and Management Research, 2025)
Over the last few years, especially between 2018 and 2025, transactional finance has changed more than most people expected. What used to be a routine back-office activity has become something that directly influences how organisations manage cash, make decisions, and stay competitive. This paper looks at how automation tools and real-time payment systems have reshaped everyday finance activities and what that shift means in practice. Based on trusted secondary data, the study shows that automation can lower costs, reduce processing time, and make financial information more transparent and easier to act on. India’s examples—like UPI and GST e-invoicing help illustrate how large-scale digital systems can speed up this transformation. Similar movements in Europe and the United States suggest that the trend is global. Overall, the findings suggest that transactional finance can move beyond simple efficiency goals and start supporting business strategy. However, this transition depends on clean data, strong governance, and continuous skill development within finance teams. This paper explores how transactional finance has evolved between 2018 and 2025, focusing on automation and real-time connectivity. These developments have altered traditional accounts payable, accounts receivable, and liquidity-management processes. Using descriptive and comparative methods based on secondary research, the study highlights the key drivers and challenges behind this shift. Verified statistics indicate faster processing, better cash-flow visibility, and changing responsibilities within finance teams. India’s government-led approach is compared with global models to show how different ecosystems can reach similar outcomes. The paper concludes with practical recommendations for organisations looking to integrate automation and real-time payment systems responsibly.